Impact of the Physical Environment on Employee Satisfaction in Private Hospitals - Roshan S. Shetty; Giridhar B. Kamath; Lewlyn L. R. Rodrigues; Nandineni Rama Devi; Sham Ranjan Shetty (Buildings)
The exponential growth of the global population and rising life expectancy have placed increasing pressure on healthcare systems to deliver efficient, high-quality, and cost-effective services. In India, private hospitals play a crucial role in meeting these demands. However, they are increasingly challenged by high employee attrition rates, often linked to dissatisfaction with the physical work environment. Improving staff satisfaction has therefore become essential for enhancing organizational performance and retaining skilled personnel. This study aims to assess the impact of the physical environment on employee satisfaction in private Indian hospitals. A mixed-methods research approach was adopted. The qualitative phase involved a review of secondary data to conceptualize the research framework and identify key variables related to architectural, interior, and ambient design features. The quantitative phase involved survey-based data collection from employees across various private hospitals. For analysis, both descriptive and inferential statistics were used to explore relationships between variables. The results reveal statistically significant relationships between physical-environment features—specifically architectural layout, interior design elements, and ambient conditions—and employees’ attitudes. These attitudes were found to significantly influence overall workplace satisfaction. Furthermore, this study confirmed a strong link between the physical environment and employee satisfaction. These findings offer actionable insights for hospital administrators to improve the design of workspaces. Enhancing physical environments can elevate employee satisfaction, reduce attrition, and ultimately contribute to improved hospital performance. By empirically establishing the link between physical-environment features and staff satisfaction, this study provides a foundation for evidence-based design strategies in healthcare settings.